Therapeutic Plants for the Management of Diarrhoea - Joel Simon, Christopher; Roy, Anitha; Duraisawamy, Revathy; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Diarrhea is one of the main water-borne diseases considered to be endemic in many regions of the world and brings the major health threats to the world populations, both in tropical and subtropical poor countries. Diarrhea is a clinical symptom of the gastrointestinal tract characterized by increased frequency of bowel movements and often in conjunction with changes in shape and consistency of stools. Diarrheal diseases are a major cause of mortality and morbidity throughout the world. Novel compounds have been discovered for their treatments. By investigating the biological activity of the extracts of such plants, their antispasmodic effects, delay in intestinal transit, suppression of gut motility, stimulation of water adsorption, or reduction of electrolyte secretion, the antidiarrheal medicinal plants have been used traditionally. Psidium guajava L., Citrus limon (L.), Mentha spicata L., Thea sinensis, and Curcuma longa L. are effectively used for the treatment of diarrhea. They are often used as a traditional medicine for the treatment of diarrhea. Diarrhea is the condition of having three or more loose or liquid bowel movements per day. The most common cause is gastroenteritis.